(untitled) (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
Competitive hotel business management emerges amidst the development of digital technology. Referring to a study by the Organization for Economic Co-operation & Development, businesses need to maximize the role of technology in creating sustainability. However, the facts show that many hotel business managers have not fully adopted technology. Several obstacles arise, including limited budget, human resource skills, and limited literacy in technology adoption. Furthermore, managers have difficulty generating creative content ideas and lack understanding of how to evaluate digital-based strategies. This study aims to investigate the digital content management of popular and high-achieving hotels in creating excellence and sustainability. Qualitative methods were used through an interpretive perspective. Several popular hotels in the Yogyakarta tourist area were selected as research objects. These hotels include: @HOM Premiere Hotel (CHSE & INDOCARE Certified), Greenhost Boutique Hotel (green promotion), and Hotel Cakra Kembang (traveler reviews). Research data were collected through semi-structured interviews. The selected informants were parties with authority, experience, and information related to the research theme. Interpretive phenomenology analysis (IPA) and triangulation techniques were chosen for data analysis and validation. The research results show that hotels need to maximize: human resource competency, appropriate use of digital platforms, creativity of content themes, intensity of publication content, internal collaboration, and communication with target markets to create sustainable and competitive management.